Is it possible to live together? Conflicts over housing in Greater Santiago - Fuster-Farfán, Xenia (Universidad Nacional de Colombia - Sede Bogotá - Facultad de Artes - Instituto de Investigaciones Hábitat, Ciudad & Territorio, 2020)
Based on case studies located in Las Condes and Peñalolén, both municipalities of Greater Santiago, an examination of the conflicts that triggers integration through subsidiary instruments promoted by the State within the framework of new guidelines for social and territorial integration. The theoretical proposal is framed in three axes: the crisis of the social link, the principle of recognition and conflicts surrounding the NIMBY phenomenon. The case studies contemplate different stages for these conflicts, which allows the delivery of a classification essay as final considerations to advance their study and contribute in the future to a policy that is still novel in the Chilean context.